Increasing Firebird Performance: strategies and good practices (Research, Society and Development, 2023)
This article aims to analyze and optimize the performance of Firebird, an open source database management system, applying the case study methodology in varied business contexts to identify effective improvement strategies, such as the proper use of indexes (including compounds), the implementation of cache, conducting fast transactions with planning and monitoring, and the correct use of parameters in the queries. The research highlights the importance of planning in creating indexes and the need for in-depth knowledge of Firebird architecture and appropriate programming techniques. In addition, the analysis also emphasizes the relevance of collaboration between developers and database administrators to ensure optimal performance. By applying the identified strategies, the results demonstrate that with careful planning and precise adjustments, it is possible to improve the performance of Firebird, making it more efficient and faster, thus providing valuable insights for its application in different business scenarios and contributing to informed decision making.